Farm to school of Park County : a journey from program to nonprofit (A) - Cates, Karen L., (SAGE business cases, 2019)
The first in a four part case series, this case describes the community, the need, and the origins of Farm to School in Livingston, Montana. The leaders of Farm to School face a budget crisis and need to evaluate four options to decide whether, when, and how it should become an independent organization.